The role of Hippo pathway in ovarian development - Zhu, Mengdi; Xu, Menghao; Zhang, Jinmin; Zheng, Cuihong (Frontiers in Physiology, 2023)
The follicle is the functional unit of the ovary, ovarian development is essentially follicular development. Follicle activation, growth and development are regulated by a variety of factors, such as reproductive endocrine system and multiple signaling pathways. Hippo pathway is a highly conserved in Drosophila and mammals. It plays an important role in cell proliferation, control of organ size, and embryonic development. During the process of follicle development, the components of the Hippo pathway show temporal and spatial variations. Recent clinical studies have shown that ovarian fragmentation can activate follicles. The main mechanism is that the mechanical signal of cutting promotes actin polymerization, which disrupts the Hippo pathway and promotes the expression of downstream CCN and apoptosis inhibitors, thereby promoting follicle development. Therefore, Hippo pathway plays an important role in follicle development and activation. In this article, we focused on the development and atresia of follicles and the role of Hippo pathway in these processes, as well as the physiological effects of Hippo pathway in the process of follicle activation.